Systemic Review to Explore the Effect of Dyslipidaemia and Metabolic Function in Coronary Heart Disease with Type 2 Diabetes Mellitus: In Tertiary Care Center - Akansha Singh; Ranjit S. Ambad; Roshan K. Jha (Journal of Pharmacy and Bioallied Sciences)
Metabolic dyslipidemia (high triglyceride) and low high-density lipoprotein cholesterol (HDL-C) are highly prevalent in type 2 diabetes mellitus (T2DM). The extent to which diabetes mellitus–related abnormalities in the triglyceride HDL-C profile associates with cardiovascular disease (CVD) risk is incompletely understood. We evaluated the associations of triglyceride and HDL-C status with CVD outcomes in individuals with T2DM. This meta-analysis aims to evaluate the effect of dyslipidaemia and metabolic function in coronary heart disease with type 2 diabetes mellitus by pooling data from multiple studies.